Cataracts: A Review - Chen, Stephanie P; Woreta, Fasika; Chang, David F (JAMA : the journal of the American Medical Association, 2025)
Age-related cataract, defined as progressive opacification or clouding of the eye's natural lens, is a leading cause of visual disability and blindness. Cataract surgery is one of the most commonly performed procedures in high-income countries. More than 3.5 million cataract operations are performed annually in the US. Older age is the primary risk factor for cataracts, with approximately two-thirds of the population older than 80 years affected. As the population ages, the number of people with cataracts in the US is expected to increase to 50 million by 2050. Additional risk factors for cataracts include a hereditary or genetic predisposition, certain medications (corticosteroids), ocular trauma, significant UV exposure or radiation therapy, and certain medical conditions such as uncontrolled diabetes, retinitis pigmentosa, Down syndrome, and congenital rubella. Painless, progressive blurring of vision and visual glare are common symptoms of cataracts. Cataracts are diagnosed during an eye examination by an ophthalmologist or optometrist. Surgery to remove the cataract and implant a permanent intraocular lens (IOL) is indicated if visual impairment impedes activities of daily living and is associated with lower rates of falls (>30%) and dementia (20%-30%). Most cataract operations are performed with topical anesthesia. Therefore, patients do not require preoperative general medical testing such as bloodwork or electrocardiogram, and do not need to discontinue anticoagulants for cataract surgery. Systemic α1-adrenergic antagonists for symptomatic benign prostatic hyperplasia, such as tamsulosin, increase the risk of surgical complications and some ophthalmologists temporarily discontinue the drug preoperatively. Intraocular antibiotics, such as moxifloxacin or cefuroxime, delivered intraoperatively have reduced the rates of sight-threatening postsurgical endophthalmitis from 0.07% to 0.02%. In addition to reversing and preventing progressive vision loss, cataract surgery can reduce dependence on eyeglasses. These optional refractive benefits are achieved with advanced technology IOL designs, such as multifocal IOLs. However, multifocal and other advanced technology refractive IOLs are associated with increased costs that are not covered by medical insurance. Cataracts are common among older adults and may cause visual disability and blindness without treatment. Cataract surgery reverses and prevents progressive vision loss, and advanced technology lens implants facilitate reduced dependence on eyeglasses.